Efektivitas Antibakteri Hidrogel Lidah Buaya pada Treponema denticola dan Tannerela forsythia Bakteri: In Vitro - Chandra Susanto; Steven Wijaya; Ramayani Efendi; Ridha Mahrani (Lembaga Penelitian dan Pengabdian Masyarakat Akademi Keperawatan Sandi Karsa (Merger) Politeknik Sandi Karsa, 2021)
Introduction; Treponema denticola and Tannerela forsythia bacteria as the main cause of periodontal disease. The aim was to determine the effectiveness of hydrogel aloe vera with antibacterial concentrations of 2.5%, 5%, 10%, and 20% against Treponema denticola and Tannerela forsythia: in vitro bacteria. Method; is a laboratory experimental study with a post-test-only control group in vitro design. The research sample was Treponema denticola and Tannerela Forsythia. Data collection by measuring the diameter of the drag zone using a slide caliper. Data were analyzed using one-way ANOVA and LSD. Results; showed that there were differences in the hydrogel diameter of the inhibitor concentration of aloe vera 2.5%, 5%, 10%, 20%, and positive control in Treponema denticola and Tannerela forsythia bacteria. Conclusion; that there is antibacterial effectiveness of hydrogel aloe vera concentrations of 2.5%, 5%, 10%, and 20% in Treponema denticola and Tannerela forsythia bacteria.